Preparation of CuInS2/TiO2 nanotube heterojunction arrays electrode and investigation of its photoelectrochemical properties - Li, T.; Li, Xin Yong; Zhao, Q.; Teng, W. (Elsevier Ltd, 2014)
CuInS2/TiO2 nanotube heterojunction arrays electrode was synthesized via a modified successive ionic layer adsorption and reaction (SILAR) method. The morphology, crystalline structure and chemical composition of the composite electrode were characterized with field-emission scanning electron microscopy (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectra (XPS), respectively. The optical properties were investigated by UV-vis diffusion reflection spectra (DRS) and photoluminescence (PL) spectra as well as the photoelectrochemical measurements. Significantly enhanced photoelectrochemical properties of CuInS2/TiO2 NTs electrode were observed under visible light irradiation, which could be attributed to the high absorption coefficient of CuInS2 in visible region and the heterostructure formed between CuInS2 and TiO 2. © 2014 Elsevier Ltd.